Unlocking the Potential of Receptor-Based Approaches in Diabetes Treatment - Mohsina Patwekar; Faheem Patwekar; J. Pavan Kumar; P. Dharani Prasad; Nazia Malik; A. Venkata Badarinath; Prashanth Parupathi; Konatham Teja Kumar Reddy; Selvaraja Elumalai; Zainul Abedeen Ab Samad (BIO Integration)
Diabetes, a common metabolic condition, poses a substantial health burden worldwide. To revolutionize diabetes management, enhance glycemic control, and decrease the risk of complications, recent research has revealed innovative targets and therapeutic options. A thorough examination of modern drugs that target particular receptors and metabolic pathways for glucose and fat metabolism is presented. Recent research has revealed innovative targets and therapeutic options. Liraglutide, a GLP-1 receptor agonist, has been shown to effectively lower glucagon levels and promote weight loss. Empagliflozin is a sodium-glucose co-transporter 2 (SGLT2) inhibitor with substantial promise in decreasing blood glucose levels, and providing cardiovascular and renal advantages. Pegbelfermin (BMS-986036), a fibroblast growth factor 21 (FGF21) analogue, is being investigated for its ability to regulate glucose and lipid metabolism, and potentially enhance glycemic control and lipid profiles. Additionally, G-protein-coupled receptor (GPCR) agonists and adenosine monophosphate-activated protein kinase (AMPK) activators are emerging as potential medicines to improve insulin sensitivity, glucose uptake, and insulin signaling pathways. Despite being in early research stages, bile acid receptor agonists and mitochondrial uncouplers have promising potential for modifying lipid and glucose metabolism. The long-acting insulin analogue insulin glargine, which replaces basal insulin, continues to be a cornerstone of advanced diabetes management. In the future, these medications are expected to be improved through the use of combination therapy and personalized, precision medicine. Gene therapies show promise as novel strategies to address genetic defects and provide potential treatments. Additionally, patient monitoring, adherence, and self-management will be greatly aided by the integration of digital health technology, telemedicine, and artificial intelligence (AI), thus leading to better treatment outcomes and patient quality of life. Healthcare professionals, researchers, politicians, and patients working together will pave the way to substantial improvements in the management of metabolic disorders including diabetes. In conclusion, hope for more efficient, individualized, and secure therapies may come from continuing research and breakthroughs in novel diabetes treatment targets. These developments are at the forefront of offering people with diabetes and related metabolic disorders a better and healthier future, by revolutionizing diabetes management.